Physical activity, climate change and health: a conceptual model for planning public health action at the organizational level - Schneider, Sven; Winning, Alexandra von; Grüger, Fiona; Anderer, Stefan; Hoffner, Robert; Anderson, Lilian Marie (International journal of environmental research and public health, 2022)
Climate change is linked to health risks for both professional and amateur athletes. Sports organisations will need to react to these developments. The starting point for this concept paper is a summary of the sport-specific health risks currently under discussion: increasing heatwaves, growing numbers of extreme weather events, rising UV, ozone and allergen levels and the spread of infectious diseases. Based on the current state of research, a conceptual model is developed to reduce these climate-related health risks in sports at organisational level. Given the wide variety of predicted direct and indirect health risks linked to climate change, the “sports, clubs and climate change model” (SC3 model) presented here follows a stepwise risk-specific approach using technical, organisational and person-related measures. The SC3 model also includes cross-cutting measures that have an overarching effect comprising training, warning systems, coordination and evaluation measures. The SC3 model makes it possible to develop prevention plans, both at national level for central associations and at the regional level of local organisations and clubs. It can be applied to typical settings (e.g., training or competition at elite or amateur levels) and target groups (e.g., athletes, spectators, referees and club officials).